Excessive Dietary Lipid Affecting Growth Performance, Feed Utilization, Lipid Deposition, and Hepatopancreas Lipometabolism of Large-Sized Common Carp (Cyprinus carpio) - Fan, Ze; Li, Jinnan; Zhang, Yuanyuan; Wu, Di; Zheng, Xianhu; Wang, Chang'an; Wang, Liansheng (Frontiers in Nutrition, 2021)
An 82-day study was conducted to assess the effect of the dietary lipid levels on growth performance, feed utilization, lipid deposition, and hepatopancreas lipometabolism of large-sized common carp (Cyprinus carpio). Six isonitrogenous (300 g/kg protein) pelletized diets with different dietary lipid levels (30, 60, 90, 120, 150, and 180 g/kg) were fed in triplicate to fish groups with 75 individuals (with an initial mean weight of 247.00 ± 16.67 g). The results showed that there was a significant increase in weight gain (WG) rate (WGR), specific growth rate (SGR), and protein efficiency ratio (PER) as dietary lipid levels increased from 30 to 60 g/kg (p < 0.05) and then there was a decline. Feed conversion rate (FCR) was observed to be significantly lower in 60 g/kg lipid treatments (p < 0.05). Muscle crude protein contents were obtained to be significantly higher in 60 and 90 g/kg treatments (p < 0.05). The crude lipid content in the hepatopancreas increased significantly with an increase in dietary lipid levels (p < 0.05). The expression of lipoprotein lipase (LPL) and carnitine palmitoyltransferase-1 (CPT1) in the hepatopancreas was significantly downregulated with an increase in dietary lipid levels while the expression of growth hormone (GH), insulin-like growth factor-1 (IGF-1), fatty acid synthase (FAS), acetyl-CoA carboxylase-1 (ACC-1), and sterol regulatory element binding protein (SREBP) was upregulated first in 30 and 60 g/kg lipid treatments and then downregulated significantly in other treatments. The results revealed that excess dietary lipid supplements (more than 60 g/kg) would inhibit WG and would aggravate the lipid decomposition in the hepatopancreas. Based on WGR and FCR, the dietary lipid levels of 59.5 and 70.4 g/kg were optimal for growth performance and feed utilization of large-sized common carp.